Study the Toxic Effect of Different Doses of Duprost in Liver and Blood of Albino Mice - Mohamad, Ban Jasim; Obaid, Hind Hussein; Mohamad, Duha Ibraheem; Yaseen, Maha Salim (Iraqi Journal of Science, 2021)
The aim of this study is to investigate the effect of different doses of Duprost in the liver and blood of albino mice. The current study included twenty one albino mice, obtained and grouped into 3 groups: control (3 mice), acute group (12 mice) and chronic group (6 mice). The acute group was subdivided into 4 groups and each group of 3mice, was given a lonely oral dose of (0.25ml, 0.15ml, 0.1 ml and 0.05ml respectively) for 24 hours. Whereas the third group was subdivided into 2 groups and each set was given a daily dose of (0.15ml and 0.05 ml respectively) for 30 days. After the mentioned periods, blood samples from each animal were taken for blood analysis. Then, the mice of all groups were sacrificed and the livers were removed, processed, sectioned and stained for histological analysis. In acute group, all mice that dosed with (0.25 ml) dose, died after 15 minutes of dosing. Blood results showed significant decrease in Hb level, WBC’s and platelets’ count among acute subgroups in comparison with chronic subgroups which showed significant increase in WBC and platelets’ count, but a significant decrease in Hb levels. The histological analysis of liver in acute subgroups showed different forms of liver inflammation among acute subgroups, in comparison with chronic subgroups which showed formation of granulomatous lesions in the liver parenchyma in high dose(0.15ml) but there were inflammatory cells’ aggregation in liver parenchyma among lower doses.